2010
DOI: 10.1152/ajpendo.00448.2009
|View full text |Cite
|
Sign up to set email alerts
|

The microRNA miR-696 regulates PGC-1α in mouse skeletal muscle in response to physical activity

Abstract: T. The microRNA miR-696 regulates PGC-1␣ in mouse skeletal muscle in response to physical activity. Am J Physiol Endocrinol Metab 298: E799 -E806, 2010. First published January 19, 2010 doi:10.1152/ajpendo.00448.2009 are small noncoding RNAs involved in posttranscriptional gene regulation that have been shown to be involved in growth, development, function, and stress responses of various organs. The purpose of this study was to identify the miRNA response to physical activity, which was related to functions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
137
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 52 publications
1
137
0
4
Order By: Relevance
“…This suggests that inhibition of PARP activities is beneficial to promote skeletal muscle energy expenditure. One promising strategy to inhibit the activity of endogenous PARPs would be modulation of the miRNA-mediated pathway, which plays a key role in skeletal muscle metabolism (22,(29)(30)(31)(32)(33). To achieve this, we attempted to identify miRNAs that control PARP expression.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that inhibition of PARP activities is beneficial to promote skeletal muscle energy expenditure. One promising strategy to inhibit the activity of endogenous PARPs would be modulation of the miRNA-mediated pathway, which plays a key role in skeletal muscle metabolism (22,(29)(30)(31)(32)(33). To achieve this, we attempted to identify miRNAs that control PARP expression.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-696 negatively regulates expression of PGC-1a protein 12 and Western blots indicated that all anti-miR treatments significantly increased PGC-1a protein expression compared to negative control (Fig. 1C, D).…”
Section: Microrna Inhibition In 2d Cultures Accelerates Myogenesis Anmentioning
confidence: 89%
“…38 Aoi et al found that levels of PPARGC1A were unchanged for miR-696 overexpression and inhibition. 12 Likewise, in 2D and 3D culture, PPARG-C1A expression was unchanged following miR-133a and miR-696 inhibition. Results are consistent with miR-133a and miR-696 inhibiting the initiation of PGC-1a translation.…”
Section: Fig 5 Isometric Force Testing Of Muscle Bundles (A)mentioning
confidence: 94%
See 1 more Smart Citation
“…1). Interestingly, all of these miRNAs are regulated by exercise (16)(17)(18). Since both exercise and caloric restriction are linked to increased SIRT-1 activity and improved mitochondrial function, it will be interesting to investigate whether miR-149, and by extension also PARP-2, is differentially regulated in these metabolically beneficial states.…”
mentioning
confidence: 99%